2015
DOI: 10.1111/jch.12714
|View full text |Cite
|
Sign up to set email alerts
|

High Blood Pressure and Related Factors Among Individuals at High Risk for HIV/Sexually Transmitted Infections

Abstract: Data from a social network-based HIV/STI prevention study with a total of 330 men and women at high risk of HIV/STIs were used to examine the relationships of substance use, depressive symptoms, general health, cardiovascular disease risk factors, sociodemographic characteristics, and systolic/diastolic blood pressure (SBP/DBP). Approximately 60% of the participants had prehypertension to stage 2 hypertension. In the base model, older subjects (p<.0001), men (p=.003), and with poorer self-reported health (p=.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…If human regarded as whole, the thoughts, perspectives and practices affect his body and soul directly or non-directly. Many philosophical, religious documents and excellent scientific findings in psychology, biology and medicine favor it [4]. Therefore, human health is influenced by lifestyle, also.…”
Section: The Influence Of Lifestyle On Different Aspects Of Human Lifementioning
confidence: 99%
See 4 more Smart Citations
“…If human regarded as whole, the thoughts, perspectives and practices affect his body and soul directly or non-directly. Many philosophical, religious documents and excellent scientific findings in psychology, biology and medicine favor it [4]. Therefore, human health is influenced by lifestyle, also.…”
Section: The Influence Of Lifestyle On Different Aspects Of Human Lifementioning
confidence: 99%
“…The emphasis on limitation of meat consumption to the amount of human requirement VIII. -Emphasis on beneficial and curative effect of honey for human health It is suggested that Islamic lifestyle in nutrition, expresses beneficial effects for normal nutrition and prevention of obesity and nutritional disorders and therefore heart health [4]. Some traditional foods as recommended foods in Islam may be essential role in people health and longevity.…”
Section: Diet and Nutrition Stylementioning
confidence: 99%
See 3 more Smart Citations